Development and Validation of a Pain Competence Assessment Tool (PCAT) Based on the IASP Core Competencies for Pain Management - Samah Hassan; Andrea Furlan; Bonnie Stevens; Judy Watt-Watson; Sharon Switzer-Mcintyre; John Flannery (Taylor & Francis Group, 2019)
Several interprofessional education programs have been developed to enhance primary care providers' (PCPs) competency in pain management. This project aims to develop a valid and reliable competency-based assessment tool, suitable for all professions, to evaluate the impact of these programs. To develop a new pain competence assessment tool (PCAT), six clinical vignettes were created. Each vignette is followed by questions addressing one or more competencies derived from the core pain competencies developed by Fishman et al. in 2013. Experts in pain management representing different professions were asked to review and rate the appropriateness of the PCAT questions to confirm face validity through a modified Delphi study. The selected PCAT questions were mapped against the core competencies to ensure content validity. A pilot sample of PCPs was then asked to answer the PCAT through a cognitive interview study to assess feasibility. Currently, the PCAT was sent to a large sample of PCPs to assess its reliability through a cross-sectional study. The PCAT was also sent to healthcare prelicensure students to test for construct validity. Based on the Delphi results, nineteen questions were rated as appropriate confirming its face and content validity. The PCAT also showed adequate feasibility based on the cognitive interview study. Psychometric testing is still in process. Future implementation of a valid and reliable tool is necessary to reduce measurement error and produce results with high degree of credibility. Introduction/Aim: Several interprofessional education programs have been developed to enhance primary care providers' (PCPs) competency in pain management. This project aims to develop a valid and reliable competency-based assessment tool, suitable for all professions, to evaluate the impact of these programs. Methods: To develop a new pain competence assessment tool (PCAT), six clinical vignettes were created. Each vignette is followed by questions addressing one or more competencies derived from the core pain competencies developed by Fishman et al. in 2013. Experts in pain management representing different professions were asked to review and rate the appropriateness of the PCAT questions to confirm face validity through a modified Delphi study. The selected PCAT questions were mapped against the core competencies to ensure content validity. A pilot sample of PCPs was then asked to answer the PCAT through a cognitive interview study to assess feasibility. Currently, the PCAT was sent to a large sample of PCPs to assess its reliability through a cross-sectional study. The PCAT was also sent to healthcare prelicensure students to test for construct validity. Results: Based on the Delphi results, nineteen questions were rated as appropriate confirming its face and content validity. The PCAT also showed adequate feasibility based on the cognitive interview study. Psychometric testing is still in process. Discussion/Conclusions: Future implementation of a valid and reliable tool is necessary to reduce measurement error and produce results with high degree of credibility.